Surgical Treatment of Finger Degloving Injuries Without Usable Skin: a Case Report and Literature Review - Stulpinas, Agnius; Venciūtė-Stankevičė, Rūta; Jakutis, Nerijus (Lietuvos chirurgija, 2022)
The treatment of avulsion injuries of the fingers is complicated by the lack of universally accepted treatment guidelines and the wide variety of reconstruction techniques. The aim of this paper is to present a case and review the scientific literature to provide clear criteria for amputation and reconstruction and to present and discuss the reconstruction techniques with the best results.